Progressive Collapse of Typical and Atypical Reinforced Concrete Framed Buildings - Solomon Abebe Derseh; Tesfaye Alemu Mohammed; Girum Urgessa (International Journal of Concrete Structures and Materials)
Abstract This paper investigates the progressive collapse potential of eight-story reinforced concrete framed buildings with several atypical structural configurations and compares results with a typical structural configuration. The alternative load path mechanism, the linear-static analysis procedure amplified by dynamic increase factors, and the demand capacity ratio criterion limits from the U.S. General Services Administration guideline were used to evaluate the vulnerability of the different atypical and typical framed structures. Variations in bay size, plan irregularity, and closely spaced columns were used to represent the atypical structural configurations. The extracted demand-capacity ratio (DCR) of the global structural response showed that the demand-capacity ratio for the longitudinal frame with short-span beams had a larger DCR than the transverse frame with longer beam spans with significant potential for progressive collapse. Furthermore, atypical building configurations with closely spaced columns failed by shear and showed the highest DCR limits. In addition to the global structural response, the local member end actions were also evaluated. The evaluation showed that the critical atypical frame configuration with closely spaced columns had a 91% and 127% maximum shear force and support bending moment value difference, respectively, when compared to a baseline typical frame configuration.